"Enrico IV" ovvero il potere salvifico dell’immaginazione - Brunetti, Simona (Mimesis Journal, 2015)
Among the writings published by Umberto Artioli a year before his sudden death in July 2004, there is a study on Luigi Pirandello’s Enrico IV. Abandoning the usual realistic interpretation of the text, the scholar highlights the allegorical path underneath its conception and a number of references related to the evangelical Last Supper. The core of Pirandello’s hero teachings identifies in the theatrical imagination the way to salvation. Although the initiation of his disciples fails, the Author outlines the characteristics of a new type of artist and his ideal relationship with the public; a figure that will inspire Bontempelli’s ideas on an extremely versatile and eclectic interpreter to be driven on stage like a puppet.